PENGENDALIAN PEMBANGUNAN PADA KAWASAN SEMPADAN JURANG DI SEPANJANG JALAN RAYA PENELOKAN KINTAMANI - Made Reiza Maharani Augustiningsih; I Made Sudirga (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2023)
Spatial use control is carried out in accordance with the Spatial Plan to reduce violations. In writing this thesis, it is necessary to review the implementation of spatial use control and the constraints faced by the Bangli Regency Government in implementing it. The type of research used in this research is empirical legal research. The approaches used are the legal sociology approach, the legal anthropology approach, and the legal psychology approach. The results obtained in this study are that the implementation of controlling the use of space in the ravine area is not effective and tends to be neglected. Then the obstacles faced by the Government of Bangli Regency in controlling the use of space for the rampant development in the ravine area are caused by several factors, namely legal factors, law enforcement factors, supporting facilities and facilities, community factors and cultural factors.